General Theory of Library Classification and Classifying According to UDC - Bhattacharyya, G. (Journal of Information and Knowledge, 1972)
A classified catalogue lias to be based oil a scheme for classification. The basis of the design of a classified catalogue is "Classifying". UDC is primarily meant to serve as a basis for designing a classified catalogue. Classifying according to UDC is examined in the light of the postulates for facet analysis and the principles for determining facet sequence, forming part of the General Theory of Library Classification developed by S R Ranganathan in his Prolegomena to library classification. For this purpose, the principles, governing the development of UDC in its formative stage, are distilled out from the "General Introduction", Outline Structure, Auxiliary Tables and from the schedules. Each distinctive feature of UDC is correlated to the relevant basic principles. The devices prescribed by UDC for classifying in conformity with its basic principles are discussed with illustrative examples. Classifying according to TJDC, for designing a Multiple Entry Classified Catalogue is demonstrated and the disadvantages of the latter are mentioned. The Single Entry System prescribed by the Guide to UDC (1963) is discussed. The principles for determining the Facet Sequence in a compound subject, prescribed by the Guide, are examined. It is shown that each of these principles has a corresponding postulate or principle, as the case may be, in the General Theory of Library Classification. This General Theory may be adopted by any scheme for classification for its design and development. For example, CC has adopted this. This General Theory has prescribed the Postulational Method of Classifying. An examination of the principles, for determining the facet sequence in a compound subject, as prescribed by the Guide indicates that it intends to recommend the Postulational Method of Classifying, though inadequately, as prescribed by the General Theory of Library Classification. It is shown that UDC has the necessary "flexibility" for being adapted for this purpose, though at the cost of some economy and effectiveness. To ensure economy and effectiveness, much rethinking on the design and development of UDC will be necessary. The use of the Postulational Method of Classifying by UDC is demonstrated with an example.